Prevalence of Carbapenemase Genes, qacE, qacEΔ1 and cepA in Multidrug-Resistant Gram-Negative Bacteria with Different Susceptibility to Chlorhexidine - K. G. Kosyakova; N. B. Esaulenko; O. A. Kameneva; S. P. Kazakov; A. Y. Dubinina; E. Y. Mezina; A. A. Zaitsev (Эпидемиология и вакцинопрофилактика)
Relevance The World Health Organization has provided a list of resistant bacteria that pose the greatest threat to society. Among them, the most important (critically high priority level) are Pseudomonas aeruginosa and Acinetobacter baumannii strains resistant to carbapenems, as well as enterobacteriaceae producing extended spectrum beta-lactamases and carbapenemases.Aim. To conduct a comparative analysis of the sensitivity to chlorhexidine of multiply-resistant gram-negative bacteria, the causative agents of infectious conditions in patients of various medical organizations, and to study the relationship between the presence of resistance genes and the minimum inhibitory concentration of chlorhexidine.Materials & methods. The study included 138 Gram-negative multidrug-resistant strains isolated during 2018–2019 from various clinical specimens. Susceptibility of the isolates to antibiotics were determined using Vitek-2 compact and Phoenix М50, susceptibility to chlorhexidine were determined by agar dilution method. The resistance genes were detected by the real-time PCR method.Results. The lowest level of resistance to chlorhexidine was determined in E. coli strains (MIC90 16 mg/l), other strains were highly resistant: MIC90 of P. aeruginosa and A. baumannii – 128 mg/l, K. pneumoniae, E. cloacae и P. mirabilis – 256 mg/l. The highest frequency of detection of carbapenemase genes observed in K. pneumoniae strains – 56.0% and P. aeruginosa – 48.1%. High prevalence of cepA gene was found out (the strains of enterobacteria – 47.8%, A. baumannii – 42.9%), genes qacE, qacEΔ1 were more often detected in non-fermenting Gram-negative bacteria then in enterobacteria. Conclusion. According to the results of our study, we did not reveal a significant correlation between the presence or absence of resistance genes and MIC of chlorhexidine in Gram-negative bacteria. However, taking into account complex mechanism of the adaptive response of bacteria to the effects of chlorhexidine, and to implement the concept of preventing health care-associated infections, it is proposed to continue dynamic monitoring of the resistance of microorganisms to antiseptics, disinfectants and antibiotics.